Respuesta :

DWRead

Answer:

Step-by-step explanation:

(1) 2x - 6y = -12

(2) x + 2y = 14

There is a -6y and a +2y. Since they have opposite signs, I'll try to eliminate the y terms. (That's my choice. There is more than one way to solve these.)

Multiply eq. (2) by 3:

3x + 6y = 42

Then add the result to eq. (1) to eliminate the y terms:

2x - 6y = -12

3x + 6y = 42

------------------

5x   = 30,  so x = 6

Now plug the value of x into eq. (2) and solve for y:

6 + 2y = 14

2y = 8

y = 4

Why did I use eq. (2) to solve for y? Because it's less work. I could have used eq. (1) instead:

2(6) - 6y = -12

12 - 6y = -12

-6y = -24

y = 4

More than one way to solve.